The Impact of Immigration on the Structure of Male Wages: Theory and Evidence from Britain - Marco Manacorda; Alan Manning; Jonathan Wadsworth (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
Immigration to the UK has risen over time. Existing studies of the impact of immigration on the wages of native-born workers in the UK have failed to find any significant effect. This is something of a puzzle since Card and Lemieux, (2001) have shown that changes in the relative supply of educated natives do seem to have measurable effects on the wage structure. This paper offers a resolution of this puzzle - natives and immigrants are imperfect substitutes, so that an increase in immigration reduces the wages of immigrants relative to natives. We show this using a pooled time series of British cross-sectional micro data of observations on male wages and employment from the mid-1970s to the mid-2000s. This lack of substitution also means that there is little discernable effect of increased immigration on the wages of native-born workers, but that the only sizeable effect of increased immigration is on the wages of those immigrants who are already here.
Keywords: J6; 330; Wages; Wage Inequality; Immigration